APLICAÇÃO PRÁTICA DAS DIRETRIZES DA ACV NA ARQUITETURA: AVALIAÇÃO PILOTO DO USO DE FERRAMENTA BIM ASSOCIADA A ACV NAS TOMADAS DE DECISÕES DE PROJETO - Carvalho, Tathiana; Silvoso, Marcos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The intense growth of construction has caused impacts on the economy and the environment, mobilizing the development of applicable tools in projects. The Life Cycle Assessment (LCA), when applied to the technical specification stage can contribute to the identification of opportunities for improvement and assistance in decision making, evaluating environmental indicators of the materials. The increasing use of digital tools in construction stimulates its association with LCA, given that the BIM platform proposes to facilitate and speed up the sharing of information, facilitating decision making. The objective of this article, a partial result of research in an academic master's degree, is to present the results of the development of pilot evaluation of single-family housing in Minha Casa Minha Vida, using the software Autodesk Revit® and Simapro® (Ecoinvent® base). Although the information in Ecoinvent 3.3 is not adapted to the Brazilian reality, it was possible to simulate and verify how the analyzes are carried out and which inputs would most impact the habitation. For the next phase will be used data from the national literature, verifying the possibility of insertion in 3D modeling, as well as to deepen knowledge of the contribution of transport from the industry to the construction site.